2023
DOI: 10.1111/jnu.12874
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychological flexibility in the relationships between burnout, job satisfaction, and mental health among nurses in combatting COVID‐19: A two‐region survey

Abstract: BackgroundA growing body of evidence suggests that the COVID‐19 pandemic is adversely impacting the mental health and well‐being of frontline nurses worldwide. It is therefore important to understand how such impact can be mitigated, including by studying psychological capacities that could help the nurses regulate and minimize the impact.AimTo examine the role of psychological flexibility in mitigating the adverse impacts of burnout and low job satisfaction on mental health problems (i.e., anxiety, depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…This study emphasized the importance of addressing HCW mental health needs, especially those with prior diagnoses of mental illness, to mitigate insomnia during the COVID-19 pandemic [21] . Moreover, other studies have shown the importance of interventions, including organizational support, psychosocial support, and enhancing psychological flexibility, which can mitigate the adverse effects of burnout [22] [25] . In addition, educational attainment, job satisfaction, intrinsic motivation, and loyalty (i.e., “we are family” theme among HCW and value of supportive collegial relationships as well as supportive working environments) play an important role in coping with stress related to COVID-19 [22] [25] .…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…This study emphasized the importance of addressing HCW mental health needs, especially those with prior diagnoses of mental illness, to mitigate insomnia during the COVID-19 pandemic [21] . Moreover, other studies have shown the importance of interventions, including organizational support, psychosocial support, and enhancing psychological flexibility, which can mitigate the adverse effects of burnout [22] [25] . In addition, educational attainment, job satisfaction, intrinsic motivation, and loyalty (i.e., “we are family” theme among HCW and value of supportive collegial relationships as well as supportive working environments) play an important role in coping with stress related to COVID-19 [22] [25] .…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…One study was open-label randomized controlled trial ( 21 ), and one study utilized a quasi-experimental design ( 22 ). The research had taken place across 20 different countries, with two of the studies being multi-national ( 23 , 24 ). The countries that were part of this review included Bangladesh, Brazil, Canada, China, Egypt, Germany, Great Britain, Hong Kong, Iran, Israel, Italy, Philippines, Poland, Portugal, South Korea, Spain, Sweden, Switzerland, Turkey, and the United States.…”
Section: Resultsmentioning
confidence: 99%
“…The 23 included studies employed a diverse set of measurement tools to evaluate job satisfaction. Among these tools were the McCloskey/Mueller Satisfaction Scale ( 23 , 26 ), the Minnesota Satisfaction Questionnaire ( 25 ), the Turkish Job Satisfaction Scale ( 31 ), the Job Satisfaction Scale ( 24 ), the Safety Attitudes Questionnaire ( 32 ), the Nursing Questionnaire on Organizational Health ( 22 ), and the Brayfield and Rothe’s 5-item Short Index of Job Satisfaction ( 33 ). Some of the researchers though opted for a single item scale to gauge job satisfaction ( 27 , 29 , 30 , 34 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Evidence suggests that a psychiatric epidemic is cooccurring with the COVID-19 pandemic, 4 which may necessitate attention to improving access to psychotropic drugs. Several psychopathologies, such as anxiety and depression, 5,6 increased during the pandemic in addition to other conditions, including burnout 7 and post-traumatic stress disorder. 8 Eating disorders and violence rates also grew, requiring substantial management through psychotropics.…”
Section: Introductionmentioning
confidence: 99%